Effects of different adding methods of fermentation medium on the quality of cigar - Wen, Cai; Shuanghong, Yang; Wanrong, Hu; Ran, Chen; Zhishun, Chai; Danqun, Huo; Changjun, Hou; Dongliang, Li; Qianying, Zhang (Frontiers in Bioengineering and Biotechnology, 2024)
To investigate the effects of different media and media addition methods on the fermentation of tobacco. [Methods] A plant extract and a bacterial agent are used for fermenting cigar tobacco leaves in a different order of addition. The chemical composition, cellulose, and pectin content, as well as changes in the microbial community, were measured. [Results] The addition method of the fermentation medium affects the quality of fermented tobacco. The optimal medium formula and addition method involve first adding plant extracts and then microbial agents. The medium formula and addition method can significantly reduce cellulose in tobacco, with a reduction rate of 46%, and significantly increase the content of βcarotene, thereby enhancing the aroma of cigarettes. There is an increase in aroma components, such as alcohols, alkanes, and olefins, in tobacco. By reducing the proportion of Aspergillus, it can alter the microbial community structure of tobacco.[Conclusion] Adding plant extracts before introducing microbial agents can significantly improve the quality and alter the microbial community structure of Dexue No.1 tobacco.